(3GdQCj GdYGe Hjf GdbhI GdfGYeI hGdbhI GdNTfI (B/s - (3ScQj, Qajbs ((3WQGHdS, dHfGf ;s (3HjQhJ (B:s (3GdeDSSI GdMOjKI ddcJGH,s, 2012)
(3jMed gPG GdcJGH QZHI GdHGMK hGdeacQ aj aJM GdBaGb CeGe GdbQGA hHGdPGJ CeGe GdWdHI dXGgQI bjGOI hUfGYI GdQCj GdYGe efP GdfTCI GdJGQjNjI dgPg GdXGgQI Gdi WQb bjGSgG hUhdG Gdi hGbY GdJCKjQ GdSjGSj GdeYGUQ HXGgQI GdTGFYI hYdjgG Cj eG jYQa HGdOYGjI GdSjGSjI, eQhQG ObI GdJhKjb hGdeQGLY hfHV GdHGMK GdYQHj hGfaJGMg Ydi GdYGde jLYd ef bQGAI gPG GdcJGH eJYI JUMH GdaGFOI GdYdejI(B.s
(3HHdjhLQGajI (B: (3UaMI (B353-374.s
Keywords: (3GdCMRGH GdSjGSjIs; (3GdOYGjI GdSjGSjIs; (3GdQCj GdYGes